Core Description and Characteristics of Fault Zones from Hole-A of the Taiwan Chelungpu-Fault Drilling Project - En-Chao Yeh; Hiroki Sone; Taichi Nakaya; Ka-Hao Ian; Sheng-Rong Song; Jih-Hao Hung; Weiren Lin; Tetsuro Hirono; Chien-Ying Wang; Kuo-Fong Ma; Wonn Soh; and Masataka Kinoshita (Terrestrial, Atmospheric and Oceanic Sciences, 2007)

(untitled)
Taiwan Chelungpu-fault Drilling Project was conducted in drill site Dakeng, Taichung City of central western Taiwan during 2004 - 2005 principally to investigate the rupture mechanism in the northern segment of the Chi-Chi earthquake of 21 September 1999, and also to examine regional stratigraphy and tectonics. Core examination (500 - 1800 m) of Hole-A gave profound results aiding in illustrating the lithologic column, deformation structure, and architectural pattern of fault zones along the borehole. Lithology column of Hole-A was identified downward as the Cholan Formation (500 - 1027 m), Chinshui Shale (1027 - 1268 m), Kueichulin Formation (1268 - 1712 m), and back to the Cholan Formation (1712 - 2003 m) again. A dramatic change is observed regarding sedimentation age and deformation structure around 1712 m. Along the core, most bedding dips _ _ Around 1785 m, bedding dip jumps up to _ the bottom of borehole. Five structure groups of different orientations (dip direction/dip) are observed throughout the core. Based on the orientation and sense of shear, they are categorized as thrust (105/30), left-lateral fault (015/30 - 80), right-lateral fault (195/30 - 80), normal fault (105/5 - 10), and backthrust (285/40 - 50). Ten fault zones have been recognized between 500 and 2003 m. We interpret the fault zone located at around 1111 m as being the most likely candidate for rupture deformation during Chi-Chi earthquake. The fault zone seated around 1712 m is recognized as the Sanyi fault zone which is 600 m beneath the Chelungpu fault zone. Ten fault zones including thrust faults, strike-slip faults and backthrust are classified as the Chelungpu Fault System (<1250 m) and the Sanyi Fault System (>1500 m). According to the deformation textures within fault zones, the fault zones can be categorized as three types of deformation: distinct fracture deformation, clayey-gouge deformation, and soft-rock deformation. Fracture deformation is dominant within the Chelungpu Fault System and abother two architectures prevail in the Sanyi Fault System. The fracture deformation pattern is asymmetric, which depended the shear sense of fault zone. From the core examination of TCDP Hole-A, the lithology plays an important role in controlling the location and deformation of fault zones.